2015
DOI: 10.1007/s11192-015-1668-5
|View full text |Cite
|
Sign up to set email alerts
|

Growing trend of China’s contribution to haze research

Abstract: In past 15 years, haze has become one of the most concerned environmental problem in China. This study examines China's performance on haze research using scientometrics indicators such as China's global publication share, rank, growth rate and citation impact, its publications in various areas, top journals based on last 15 years (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014) publications data obtained from ISI Science citation index expanded database. Chinese share… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…All of these research findings could provide foundation to understand the research developing process and trends in haze analysis for researchers in the field of haze. Yang et al (2015) first examined publication share, growth rate, and top journals of research on haze by using scientometrics approach. However, the method of the paper is only statistical analysis and the study area is constrained within China.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All of these research findings could provide foundation to understand the research developing process and trends in haze analysis for researchers in the field of haze. Yang et al (2015) first examined publication share, growth rate, and top journals of research on haze by using scientometrics approach. However, the method of the paper is only statistical analysis and the study area is constrained within China.…”
Section: Discussionmentioning
confidence: 99%
“…The figure showed that countries/territories in the northern hemisphere participating in haze research were more than that in the southern hemisphere. On one hand, academic cooperative connections among countries/territories in the northern hemisphere were relatively concentrated; on the other hand, in recent years, the fact that some countries/territories including China, India, Russia, South Korea, and Belgium (Yang et al 2015) have been facing severe air pollution problem indirectly reflected that air quality in the northern hemisphere was worse than that in the southern hemisphere. As a result, scholars in the northern hemisphere took close attention to study air pollution problem including the haze phenomenon.…”
Section: Countries/territoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies focus, using bibliometric approaches, on the internationalization of Chinese journals (Wang, Wang and Weldon 2007;He and Liu 2009), or on the production and citation impact of Chinese authors within a single journal (Yan, Rousseau and Huang 2016). The bibliometric performance of China within different scientific fields has also been studied (Huang et al 2015;Sun and Hua 2015;Yan and Sun 2015;Yang et al 2015), as well as university-industry co-publishing (Fan, Yang and Chen 2015) and university-industry-research institute copublishing (Gao, Guo and Guan 2014) in China. Chinese science policy, including the role of KLs, is discussed in (Benner, Liu and Serger 2012).…”
Section: Previous Researchmentioning
confidence: 99%
“…This paper focuses solely on PA research in mainland China. A scientometric approach was employed to assess scientific disciplines internationally (Matthews 2013;Yang et al 2015;Zhang 2013). As a widely recognized bibliometric approach, measuring academic performance in science and technology, evidence suggests that scientometrics contribute significantly to social science assessment, including communication (So 2010),psychology (Guilera, Barrios, and Gómez-Benito 2012) and sociology (Cronin, Snyder, and Atkins 1997) RQ3: Who were the most frequent collaborators with mainland China and did these collaborations impact on the internationalization of Chinese PA research?…”
Section: Introductionmentioning
confidence: 99%